Green industrial policy: managing transformation under uncertainty - Wilfried Lütkenhorst; Georgeta Vidican; Tilman Altenburg; Anna Pegels (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
This Discussion Paper presents a normative concept of green industrial policy, which is defined as encompassing any policy measure aimed at aligning the structure of a country's economy with the needs of sustainable development within established planetary boundaries. The paper elaborates on the rationale of a green industrial policy, how it differs from conventional industrial policy, why it is faced with significantly bigger challenges, and how these can be met. Production and consumption patterns today are largely shaped by markets. However, markets fail to solve many of the environmental challenges the world is facing. Therefore, governments have to intervene, thus reclaiming the primacy of public policy in setting and implementing societal objectives. While safeguarding the sustainability of human life on our planet makes green industrial policy a highly normative undertaking, there is also a strong economic case for green industrial policy – the success stories of such `green' frontrunners as Germany and Denmark demonstrate the competitiveness potential of the new technologies. However, as shown by decades of discussion on industrial policy, government intervention almost invariably brings about risks of political capture and government failure. Green industrial policy is thus not only governed by ethical norms, but also by politics. The risks of failure are magnified by the urgency and scale of today's global environmental challenges, requiring particularly bold, comprehensive and well-orchestrated government intervention under high uncertainty. By highlighting lessons learned from practical cases of both success and failure, this paper shows how these risks can be, and have been, managed. This involves both the disruption of old pathways (with locked-in technologies and infrastructure as well as stranded assets) and the creation of new pathways responding to sustainability imperatives. The paper argues that a broad-based social vision needs to be forged – supported by change coalitions and coupled with policy process safeguards, openness to policy learning, and an alignment of green industrial policies with market mechanisms.
Keywords: 330; Governance; Klimawandel